The Influence of Price, Brand Image and Service Quality on Purchasing Decisions of Honda Scoopy Automatic Motorcycles (Case Study on The Koang Jaya Tangerang Community) - Sugandha; Wibowo, FX Pudjo; Janamarta, Suhendar; Tholok, Fidellis Wato (Universitas Mohammad Husni Thamrin, 2026)
This study aims to analyze the effect of price, brand image, and service quality on the purchasing decisions of Honda Scoopy automatic motorcycles among residents of Koang Jaya, Tangerang. This research examines both the partial and simultaneous influence of the independent variables—price, brand image, and service quality—on the dependent variable, namely purchasing decisions. This study employed a quantitative research method using simple random sampling. Data were collected from 100 consumers of automatic motorcycles through questionnaires, interviews, and observations. The data were analyzed using SPSS version 25, incorporating tests of reliability, validity, classical assumption tests, multiple regression analysis, t-tests, F-tests, and the coefficient of determination. The results show that price, brand image, and service quality each have a positive and significant effect on purchasing decisions. The t-test results indicate that price (t = 4.301; p < 0.05), brand image (t = 2.697; p < 0.05), and service quality (t = 3.447; p < 0.05) significantly influence purchasing decisions. Simultaneously, the F-test results (F = 45.627; p < 0.05) demonstrate that all independent variables collectively have a significant effect on purchasing decisions. The coefficient of determination (R²) of 0.815 indicates that 81.5% of purchasing decisions are explained by the independent variables, while the remaining 18.5% is influenced by other factors outside the scope of this study.